Modeling of the mimic defense based on heterogeneous redundancy - Junning QIN; Jiajia HAN; Sheng ZHOU; Chunming WU; Shuangxi CHEN; Ruoyan ZHAO; Jiangyu ZHANG (Dianxin kexue)
The unbalanced development status of network security was introduced.The main hazards and the mechanism model of penetration testing were described,and the inherent shortcomings of many existing traditional defense methods were analyzed.However,new method of the mimic defense model makes the attack information obtained invalid by dynamically selecting the executive set and adaptively changing the system composition.The same attack mode is difficult to be maintained or reproduced.Based on the attack chain model,the traditional defensetechnology and mimic defense technology were analyzed and compared,and it was demonstrated that it had a protective role in multiple stages of the attack chain.Finally,the effectiveness and superiority of the mimic defense was verified by experiments,and the model was summarized and prospected.